Structural corneal changes identified with the use of confocal microscopy after accelerated CXL for keratoconus - L.F. Troichenko; K.V. Sereda; G.I. Drozhzhyna; O.M. Ivanova; N.V. Medvedovska (Ukrainian Society of Ophthalmologists, 2020)
Background: Post-crosslinking (CXL) biomicroscopic changes in patients with keratoconus can be detected by confocal microscopy. Few studies reported on morphological changes in the cornea after CXL. Purpose: To detect structural corneal changes by confocal microscopy after accelerated CXL for keratoconus. Material and Methods: This study included 119 patients (167 eyes) who underwent accelerated CXL for keratoconus and were followed up for 12 months. Accelerated CXL was carried out using the UV-X™ 2000 Crosslinking System at an irradiation intensity of 9 mW/ cm?. Confocal biomicroscopy was performed using the Confoscan 4 unit (NIDEK Co., Ltd., Aichi, Japan). Results: Accelerated CXL (carried out in 10 minutes) for stage 2 to 3 progressive keratoconus is safe and allows stabilizing the pathological process, based on the 12-month follow-up results. At 3 months after accelerated CXL, active regeneration of keratocytes was seen in the superficial and deep stroma, with resolution of fibrotic foci. Confocal microscopy found that recovery of normal corneal architectonics started at 6 months and keratocyte repopulation was complete at 12 months after CXL.